Effect of magnesium oxide (Mgo) addition in diets for lactating holstein cows - Montaño Gómez, Martín; Salinas Chavira, Jaime; Calderón Cortés, José; Manríquez Núñez, Olga; González Vizcarra, Víctor; Ruiz Barrera, Oscar (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Arial-NormalItalic; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> It was evaluated the effect of magnesium oxide (MgO) addition in diets for Holstein cows on milk production and quality. Nineteen Holstein cows in second third of lactation were assigned to two treatments (T), with 9 and 10 animals. Both treatments were similar for days in lactation and milk yield. Cows were assigned at random to two treatments (T) groups: T1 received 0.2% and T2 received 0.4% of MgO. The MgO (alkalinizing agent) was mixed with a commercial concentrate and offered in feed bunk with total diet, which consisted of 9 kg/d of concentrate plus alfalfa hay fed ad libitum. Total diet was offered three times a day (0600; 1200 and 1700 h). The experimental period was of 30 d, with other 30 for adaptation. Milk production (kg/d) and milk quality (fat, protein, and total solids) were evaluated. Data were analyzed using the statistical package SAS through of a randomized block design. Animals on T2 (0.40% MgO) produced 2.85 kg/d more milk (P<0.50) than those on T1 (0.20% MgO). The fat, protein and total solids content in milk were higher (P<0.05) in T1 than in T2. It is concluded that the addition of 0.4% MgO in diets for lactating dairy cows resulted in milk production increased, although there was a small reduction in milk quality, compared with 0.2% MgO supplementation.